Mitochondrial-Derived Peptides Are Down Regulated in Diabetes Subjects - Ramanjaneya, Manjunath; Bettahi, Ilham; Jerobin, Jayakumar; Chandra, Prem; Abi Khalil, Charbel; Skarulis, Monica; Atkin, Stephen Lawrence; Abou-Samra, Abdul-Badi (Frontiers in Endocrinology, 2019)
Background: Mitochondrial dysfunction is implicated in the pathogenesis of Type 2 diabetes (T2D) and the development of diabetes related complications such as cardiovascular disease and stroke. Mitochondria produce several small polypeptides that may influence mitochondrial function and may impact on insulin sensitivity, such as humanin (HN) and the mitochondrial open reading frame of the 12S rRNA type-c (MOTS-c) that are mitochondrial derived proteins (MDP). The aim of this study was to determine MDP in normal, prediabetes and diabetes subjects. Subjects and measurements: In this cross-sectional study, we analyzed the serum concentrations of MDP and adiponectin (ADP) in 225 subjects: normal (n=68), pre-diabetes (n=33), T2D less than (good control; n=31) and greater than HbA1c 7% (poor control; n=93) subjects. The relationship of serum MDP and ADP concentrations with biochemical and anthropometric measurements were performed and assessed by multivariate regression. Results: Serum HN concentrations were lower in T2D (p<0.0001) and negatively correlated with age (p<0.0001), HbA1c (p<0.0001), glucose (p<0.0001), triglycerides (p<0.003), ALT (p<0.004) and TG/HDL ratio (p<0.001). Circulating HN levels were positively correlated to cholesterol (p<0.017), LDL (p<0.001) and HDL (p<0.001). Linear regression analysis showed that HbA1c and ALT were two independent predictors of circulating HN. Similarly, serum MOTS-c was significantly lower in T2D subjects compared to controls (p<0.007). Circulating MOTS-c positively correlated with BMI (p<0.035), total cholesterol (p<0.0001) and LDL (p<0.001) and negatively correlated with age (p<0.002), HbA1c (p<0.001) and glucose (p<0.002). Serum ADP concentrations were lower in T2D (p<0.002) and negatively correlated with HbA1c (p<0.001), weight (p<0.032) TG (p<0.0001) and ALT (p<0.0001); and positively correlated with HDL (p<0.0001) and HN (p<0.003). Linear regression analysis showed that HbA1c and weight were two independent predictors of circulating ADP. Multivariate analysis showed that HN and MOT-c correlated with each other, and only HN correlated with HbA1c. Conclusion: The MDPs HN and MOT-c, similar to ADP, are decreased in T2D and correlate with HbA1c. The data provide an additional evidence that mitochondrial dysfunction contributes to glycemic dysregulation and metabolic defects in T2D.